Seasonal variations of tidal currents in the deep Timor Passage - Pan, Haidong; Sun, Junchuan; Xu, Tengfei; Teng, Fei; Wei, Zexun (Frontiers in Marine Science, 2023)
Exact knowledge on the seasonal variations of main tidal constituents is beneficial for improving tidal prediction. The semi-annual cycles in K1 and S2 tides are abnormally exaggerated by astronomical P1 and K2 tides, which interferes with our understanding on tidal seasonality. The widely-used tidal inference method in previous studies cannot fully separate astronomical P1 and K2 tides from seasonal P1 and K2 tides due to inaccurate inference relationship. In this study, on the basis of the ‘credo of smoothness’ which indicates that tidal admittances are smooth functions of tidal frequencies, we develop a novel but simple method to address this intractable issue and applied this method to explore the seasonality of tidal currents observed in the deep Timor Passage at the depth of 1800m. We find that the timing and range of seasonal modulations of M2, S2, K1, and O1 tides are distinct. Annual variations in tidal currents are much stronger than semi-annual variations in tidal currents. The annual and semi-annual ranges of M2 tide can reach 2.69 cm/s and 1.51 cm/s, which are largest among main constituents. Although the annual range of K1 tide is only 1.85 cm/s, considering the relatively small amplitude of time-averaged K1 tide (2.87cm/s), K1 the most affected tide by the annual cycle. The seasonal cycles of semi-diurnal tides (M2 and S2) are basically synchronous while those of diurnal tides (K1 and O1) are generally out-of-phase. As a general method, the proposed method can be widely applied to other sea areas to explore local tidal seasonality.